Bijak dalam Menggunakan Antibiotika di Nagari Padang Laweh - Dwisari Dillasamola; Hansen Nasif; Yufri Aldi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
The high use of antibiotics inappropriately among the community today causes the problem of antibiotic resistance. Antibiotic resistance occurs when microorganisms have the ability to withstand the effects of an antibiotic drug. This can cause losses in terms of health, economy, and public health. To prevent the inappropriate use of antibiotics, education is carried out on how to use antibiotics wisely, which is good and right. The counseling method in this service activity is the lecture method where this method is good for targets with high and low education, especially the general public. The results that this service was that the community looks enthusiastic about carrying out this community service activity. The conclusion of this activity is that education and counseling can increase public knowledge about the use of antibiotics.